Is the ratio superior to the number of metastatic lymph nodes in addressing the response in patients with papillary thyroid cancer?. Issue 3 (January 2018) - Gao, Wen; Zhao, Teng; Liang, Jun; Lin, Yansong
Abstract: Context: The number of metastatic lymph nodes (LNs) and the ratio of metastatic LN (LR) have been reported as predictors of recurrence in papillary thyroid carcinoma (PTC), while the role of LR or the number of metastatic LNs on the clinical response remains unclear. Objective: We aimed to compare the prognostic value of LR and the number of metastatic LNs on clinical response in PTC. Design/Setting/Patients: A total of 384 PTC patients with LN metastases were enrolled in this study, all of whom underwent total or near total thyroidectomy and subsequent radioiodine ablation. Main Outcome Measures: After a mean follow-up of 25.7 months, response to initial therapy was classified as excellent response (ER), indeterminate, biochemical incomplete or structural incomplete response. The scatter diagram and receiver operating characteristic (ROC) curve were respectively employed to identify and compare the clinical value of the number of metastatic LNs and LR for predicting ER in different number of dissected LNs (DLNs). Multivariate analyses were further performed to explore the indicator for ER. Results: ER tended to be more concentrate in patients with lower LR and lower number of metastatic LNs in scatter diagram. Although in patients with ⩽10 DLNs, LR presented higher area under the ROC curve than the number of metastatic LNs in predicting ER (LR: 0.687, LNs, 0.556, P  = .02), whereas it turns opposite in those with >10 DLNs. In the multivariate analysis, LR (odds ratio [OR] = 1.037, P  = .001) rather than the number metastatic LNs (OR = 0.752, P  = .09) was an independent indicator for ER in addition to preablative-stimulated thyroglobulin (ps-Tg; OR = 1.056, P = .01) among patients with ⩽10 DLNs. Although in patients with >10 DLNs, the number of metastatic LNs (OR = 1.062, P  = .04) turned to be independent factor for ER, apart from ps-Tg (OR = 1.071, P  = .00) and sex (OR = 0.570, P  = .02). Conclusions: LR appears to be a better negative predictor for ER than the number of metastatic LNs in PTC patients with ⩽10 DLNs, whereas the number of metastatic LNs is superior to LR in those with >10 DLNs.